Nutrient`S Pocket Games The Effectiveness of Interactive Media in Understanding Child Nutrition in Kedungpedaringan II Kepanjen Elementary School Students - Halizah, Amilatun Nur; Risky, Aulia Dwi Nur; Yuliasari, Elly; Kharisma, Fian Ninda; Maulana Soesanto, Muhammad Ravi; Inayah, Nafisah Widhah; Setianingsih, Nida Nabilah; Amani, Revani Sabika; Cahya N, Rosalinda Syafira; Putri Hinamalua, RR Diana Septya Ningdyah; Ayara, Shofiyah Ayara; Iskandar, Syifaa Alviyana; Qurrotul `Aini, Ulya (Inovasi Lokal, 2023)
Child nutrition is important for children's physical and cognitive development. However, many children do not have a good understanding of child nutrition. Interactive media has the potential to be an effective tool to teach children about child nutrition. This study aims to determine the effectiveness of interactive media (Game Saku Gizi) in improving students' understanding of child nutrition. This study used a pre-experimental research design with a one-group pretest-posttest design. The participants of this study were a group of grade 1 to grade 5 elementary school students at SDN Kedungpedaringan II Kepanjen, Indonesia. The results showed that there was a significant difference in students' understanding of child nutrition between the pretest and posttest. This means that the useof interactive media (Game Saku Gizi) can improve students' understanding of child nutrition. Thefindings of this study have important implications for the use of interactive media in education.Interactive media can be used to develop educational games and simulations that can help students to learn about various topics, including child nutrition. However, it is important to note that interactivemedia is not a magic bullet. It is important to use interactive media along with other teaching methods,such as lectures and discussions. In addition, it is also important to choose interactive media that isappropriate for the age and learning level of the students. Based on the results of the study, it can beconcluded that the Nutritional Pocket Game can improve the nutritional knowledge of students of